МОРФОСТРУКТУРА БЕЛОМОРСКОГО РЕГИОНА - Авенариус И.Г. (My University, 2004)
The morphostructural subdivision of the White Sea region is based on morphostructural analysis of bathymetric charts, space image interpretation, data on seismicity, recent movements of the earth crust and other geological-geophysical data. Present-day morphostructural pattern of the region has resulted from the vertical and lateral Late Cenozoic differentiated tectonic movements along the complicated system of morpholineaments.
Keywords: Cenozoic; 551.432.8(470.21); Cenozoic; Кайнозой